PAYMENT FOR WORK IN THE ACCOUNTING AND ANALYTICAL INFORMATION SYSTEM OF BUSINESS ENTITIES - Vasylyuk М. М.; Chernetska , O. B. (The actual problems of regional economy development, 2024)
The article is aimed at studying the issues of formation of accounting and analytical information in the management of the efficiency of the use of the wage fund at the enterprise. The content of the concept of "salary" is characterized. It was determined that the amount of wages is determined by the complexity and conditions of the work performed, the professional and business qualities of the employee, the results of work and economic activity of the organization. The following elements of the fund were considered: basic salary fund, additional salary fund, other incentive and compensatory payments, as well as components of employee payments: wages according to salaries and tariffs, other salary allowances; payment of unworked time (annual leave and other paid unworked time); bonuses and other incentive payments paid to employees within twelve months after the start of the relevant period of employment. It was determined that the salary structure consists of the main parts of the salary, additional parts of the salary and other compensatory and incentive parts, which are organized and related to each other in a certain way. This salary breakdown is limited to basic, additional, other remuneration and incentive payments. The clarity of the definition of the components of the salary structure, the reliability and stability of receiving all payments are extremely important today, which means that a high level of financial support for each employee should lead to success and contribute to economic growth. Payroll is one of the key components of the accounting and analytical information system of any business entity. It reflects the economic relationship between the employer and the employee and includes all types of wages, bonuses, allowances and compensations that employees receive for the performance of labor duties. Wages are regulated by labor legislation, which establishes minimum guarantees regarding the level of wages, conditions for its payment, as well as norms of working hours and rest. Payroll accounting includes primary accounting: recording of time worked, work performed and calculation of wages, analytical accounting: keeping wage accounting cards for each employee, synthetic accounting: summarizing information about the calculation and payment of wages in accounting accounts. The system of accounting and analytical information of economic entities should ensure accurate and timely accounting of labor remuneration. This contributes not only to the fulfillment of legal requirements, but also to the improvement of personnel management, increasing the motivation of employees and the efficiency of the enterprise as a whole.